2020
DOI: 10.1177/0952695120945966
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological limits and the somatic significance of love: Caregivers’ engagements with neuroscience in Scottish parenting programmes

Abstract: While parents have long received guidance on how to raise children, a relatively new element of this involves explicit references to infant brain development, drawing on brain scans and neuroscientific knowledge. Sometimes called ‘brain-based parenting’, this has been criticised from within sociological and policy circles alike. However, the engagement of parents themselves with neuroscientific concepts is far less researched. Drawing on 22 interviews with parents/carers of children (mostly aged 0–7) living in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 61 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…The same was found in interviews with 22 Scottish parents who followed a parenting course in which neuroscientific information about child brain development was provided [21]. The authors found that parents adapted or rejected the neuroscientific insight based on their own needs.…”
Section: Is There Harm Done?mentioning
confidence: 63%
See 2 more Smart Citations
“…The same was found in interviews with 22 Scottish parents who followed a parenting course in which neuroscientific information about child brain development was provided [21]. The authors found that parents adapted or rejected the neuroscientific insight based on their own needs.…”
Section: Is There Harm Done?mentioning
confidence: 63%
“…Some studies used a more sociological analysis, exploring parenting norms [12,14,17]. Others used a qualitative empirical design that give insight into the experiences of parents [4,13,[18][19][20][21], adolescents [9], or policy makers [15,22]. Two studies had as primary target to review neuroscientific literature on which the neuroparenting advice are based [23,24].…”
Section: Field Analysis: Age Groups Aims Dissemination and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As existing scholarship has demonstrated, such introductions and forms of reification have happened in a range of nations. At the same time, this research has also revealed that there are limits to the extent to which accounts of the self and of distress have been neurobiologized as a consequence of the proliferation of neuroimaging ( Barnett et al., 2020 ; Broer et al., 2020 ; Pickersgill et al., 2011 ). People - including, of course, neuroscientists themselves - are often subtle and creative in whether and how they ascribe significance to the brain and imaging technologies.…”
Section: Discussionmentioning
confidence: 94%
“…Intelligence self-tests and training publications that were popular throughout the 1970s and 1980s resonate in our era’s ‘brain training games’ (Pickersgill et al , 2017). 56 Similarly, debates about parenting strategies for optimal brain development (see Broer, Pickersgill, and Cunningham-Burley, 2020; Nadesan, 2002: 411–14; Pickersgill, 2013: 329–30) cannot be disconnected from past discussions about high intelligence in children. Not coincidentally, imaginaries of cognitive enhancement and ‘smart drugs’ envision merit and distinction in one’s private and professional life through the optimized use of the mind and the brain (Bloomfield and Dale, 2020).…”
Section: Conclusion: Intelligence Knowledge and The Constitution Ofmentioning
confidence: 99%